Seven key parameters that facilitate clinical pharmacy practice: a comparison between Israel and the United States - Adam J. Rose; Daniel Witt; Carmil Azran; Ran Nissan (BMC, 2021)
Abstract Clinical pharmacists have advanced training that enables them to manage medication therapy, including prescribing, titrating, and discontinuing medications, in order to achieve therapeutic goals. In some countries, such as the United States, advances in training, responsibility, legal frameworks, and public acceptance of new roles have proceeded in parallel to expand the scope and contribution of clinical pharmacists over several decades. In this manuscript, we detail seven discrete key parameters of professional advancement for clinical pharmacists, corresponding to the seven areas in which they must advance in order to contribute fully to delivering high-quality medical care. For each key parameter, we briefly summarize the progress made in the United States to date, as well as goals for future progress. We then compare this to the development of the analogous key parameter in Israel. We found that on some key parameters, the development of clinical pharmacy in Israel lags behind the United States. This manuscript can provide a roadmap for the future advancement of clinical pharmacy in Israel, toward its full realization as a profession that can contribute to delivering high-quality medical care.